Exploring Vocational High School EFL Teacher’s Role in the Problem-based Learning: Emancipated Curriculum Context in Indonesia - Raniah Mardiant; Ika Lestari Damayanti (STAI Hubbulwathan Duri, 2024)
The shift to a PBL-oriented approach necessitates a reevaluation of the roles and identities of teachers. In the context of vocational high school English classrooms, where there may be diverse student backgrounds, aspirations, and career paths, exploring how English teachers adapt their roles as facilitators, mentors, and content experts can provide crucial insights. Additionally, understanding the factors that influence teachers' willingness and ability to embrace these roles within the context of an emancipated curriculum remains largely unexplored. Thus, this research aims to discover teachers’ role in implementing problem-based learning in the Emancipated Curriculum. This qualitative case study employed an interview to one English honorarium teacher as the main instrument, which covered the questions regarding teacher’s understanding and practice of the teacher’s role in problem-based learning. Through thematic analysis, the study revealed that, in general, the teacher’s role is in line with the previous related study, theory, and the goals of the Emancipated Curriculum in which the role of the teacher is: as the facilitator, evaluator, and guide. The findings provide practical implications for educational policymakers, school administrators, teacher educators, and English teachers seeking to enhance student engagement, motivation, and skill development in vocational education settings, specifically the findings allow teachers to learn and understand the teacher’s role in the classroom to support students in achieving problem-based learning objectives.